Starting of induction motor fed with stand-alone DFIG - M. Sharawy; Adel A. Shaltout; Naser Abdel- Rahim; Mahmoud A. Al-Ahmar; O. E. M. Youssef (Institute of Advanced Engineering and Science, 2021)
This paper presents dynamic simulation and control of stand-alone doubly fed induction generator (DFIG) loaded with 3-phase induction motors (IMs). The study reveals that direct on-line starting of large IMs causes a large voltage sag across the generator terminals as the starting current drawn reaches up to 8-9 times the rated load current. Traditionally, this problem has tackled by oversizing of the generator or employment of special starters, under the pretext of mitigating voltage sag. This work explores ways that the starting current can be reduced economically by applying constant V/f control side by side with indirect field-oriented control (FOC) applied on the rotor side converter of the DFIG. This methodology enables starting of larger IMs and mitigation of voltage sag that occurs during the start-up period. Two different rating of IMs loaded with speed-squared mechanical torque are mainly considered. Simulation results of the system behavior under study confirm the capability of the proposed control.